PENDIDIKAN MULTIKULTURAL DENGAN PENDEKATAN ADITIF DI SEKOLAH DASAR - Retnasari, Lisa; Taufik Hidayat, Muhamad (Jurnal Pendidikan Ilmu Sosial, 2018)
The plurality of Indonesians becomes a challenge for the educational world in managing people, not conflict. Until present still few people understand what is really behind the culture of the nation. Elementary School have being basic layers of education need for multicultural education ystematically. Multiculturalism education is important because for aware the students to be tolerant to diversityÂ  of Indonesian. Multicultural education can not be determined by a certain time standard, creating a plurality of tribes, races, cultures and religions to develop strengths and provide multicultural education as a national curriculum development approach. Besides, multicultural education in elementary schools can be through an additive approach.